Religion, spirituality and secularity among millennials: the generation shaping American and Canadian trends - Wilkins-Laflamme, Sarah (Routledge studies in the sociology of religion, 2023)
"This book explores the world of religion, spirituality and secularity among the Millennial generation in the U.S. and Canada, with a focus on the ways Millennials are doing (non-)religion differently in their social lives compared with their parents and grandparents. It considers the influences exercised on the (non-)religious and spiritual landscapes of young adults in North America by the digital age, precarious work, growing pluralism, extreme individualism, environmental crisis, advanced urbanism, expanded higher education, emerging adulthood, and a secular age. Based on extensive primary and secondary quantitative data, complemented with high-quality qualitative research, including interviews and focus groups, this book offers cross-national comparisons between the U.S. and Canada to highlight the impact of different social environments on the experience of religion, spirituality and secularity among the continent's most numerous generation. As such, it will appeal to scholars of religion and sociology, with interests in religious and societal change as well as in religious practice among young adults"--